Periodontal Health Status and its Impact on the Quality of Life among Diabetics attending Medical and Dental Out Patient Departments of a Tertiary Care Centre of Nepal - Bhagat, T.; Shrestha, A.; Rimal, J.; Maskey, R.; Agrawal, S.K.; Gautam, U. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: Diabetics are more prone to periodontal diseases leading to poor oral function affecting their quality of life. The objective of the study was to assess the impact of periodontal health on the quality of life among diabetics using the short version of the Oral Health Impact Profile (OHIP -14).Methods: It was a descriptive cross-sectional study. Data was collected using translated and validated Nepalese version of OHIP-14 questionnaire and clinical examination for periodontal status (Community Periodontal Index and Loss of Attachment index) was done using mouth mirror and World Health Organization probe under natural light. Data was entered and analyzed using SPSS version 11.5. Mann- Whitney U test and Kruskal-Wallis tests were used to compare OHIP-14 scores between genders and periodontal status respectively. Statistical significance was established at p